Comparing female and male perpetrators' modus operandi: victims reports of sexual abuse - Kaufman, K. L. (Journal of interpersonal violence, 1995)
Although a sizable percentage of all sexual abuse in the United States is perpetrated by females, until recently the subject of sexual offending by this population has been largely overlooked. In this study, reports of child sexual abuse by 53 victims of female perpetrators were compared with reports by a group of 53 victims of male perpetrators. Victims were matched for age, race, and sex. The purpose of this investigation was to gain information about similarities and differences in the modus operandi of female and male offenders. Females were more often involved with males in co-offender situations. They were also more likely to exploit their victims than males. Male offenders were reported to be more sexually invasive in their abuse and were more likely to use bribes to obtain victim cooperation than females